2008
DOI: 10.2337/dc08-0682
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Cardiovascular Autonomic Dysfunction in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -We investigated whether cardiovascular autonomic dysfunction was associated with glycemic control status over time in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS-From 1999 to 2000, cardiovascular autonomic nerve function testing (AFT) was performed on patients with type 2 diabetes (n ϭ 1,021) and was followed-up in 2006 and February 2008. Tests for cardiovascular autonomic functions measured heart rate variability parameters (expiration-to-inspiration [E/I] ratio, responses to the Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
1
19
0
5
Order By: Relevance
“…These include hyperglycemia induced autonomic neuropathy and resultant cardiac autonomic dysfunction 21, 22 and direct effects upon myocardial structure and function. 23 The autonomic dysfunction associated with hyperglycemia is characterized by sympathetic over-activity, cardiac denervation, increased resting heart rate, and reduced heart rate variability, 21 all markers of elevated SCD risk.…”
Section: Discussionmentioning
confidence: 99%
“…These include hyperglycemia induced autonomic neuropathy and resultant cardiac autonomic dysfunction 21, 22 and direct effects upon myocardial structure and function. 23 The autonomic dysfunction associated with hyperglycemia is characterized by sympathetic over-activity, cardiac denervation, increased resting heart rate, and reduced heart rate variability, 21 all markers of elevated SCD risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the EURODIAB study showed that the presence of retinopathy and albuminuria was associated with CAN 13. A large cohort study of 1,021 T2DM patients with CAN demonstrated that over a 7.5-year follow-up diabetic retinopathy (OR 1.513, 95% CI 1.028–2.226; P =0.036) and higher levels of micro-albuminuria (OR 1.515, 95% CI 1.031–2.228; P =0.035) predicted CAN progression 35. Similar results were found in a more recent study 36…”
Section: Can Risk Factorsmentioning
confidence: 99%
“…Several studies have indicated that the prevalence of CAN ranges from 20 to 80% in patients with type 2 diabetes (3)(4)(5). Various factors, such as increased age, diabetes duration, the presence of microvascular complications, and glycemic control status, correlate with the development of CAN (3,6).…”
mentioning
confidence: 99%